2018
DOI: 10.1038/s41541-018-0089-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the utilization of aluminum adjuvants in vaccines: you might just get what you want

Abstract: Aluminum-containing adjuvants have been used for over 90 years to enhance the immune response to vaccines. Recent work has significantly advanced our understanding of the physical, chemical, and biological properties of these adjuvants, offering key insights on underlying mechanisms. Given the long-term success of aluminum adjuvants, we believe that they should continue to represent the “gold standard” against which all new adjuvants should be compared. New vaccine candidates that require adjuvants to induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
267
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(307 citation statements)
references
References 139 publications
7
267
0
5
Order By: Relevance
“…In fact, in as early as 1926, significant enhancement of efficacy of subunit vaccines, such as the one composed of diphtheria toxoid, was successfully achieved by Glenny and colleagues through precipitation of the Ag onto alum, which has ever since been widely adopted as an efficient strategy to improve vaccine effectiveness. As a result, alum has been employed as a classical VADS to produce various types of vaccines for clinical prophylaxis of a range of pathogens and today is still given to millions of people each year [19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in as early as 1926, significant enhancement of efficacy of subunit vaccines, such as the one composed of diphtheria toxoid, was successfully achieved by Glenny and colleagues through precipitation of the Ag onto alum, which has ever since been widely adopted as an efficient strategy to improve vaccine effectiveness. As a result, alum has been employed as a classical VADS to produce various types of vaccines for clinical prophylaxis of a range of pathogens and today is still given to millions of people each year [19].…”
Section: Introductionmentioning
confidence: 99%
“…ABAs enhance vaccine effectiveness by potentiating immune responses and are widely used because they are cost-effective and in general have a good safety profile. Because of this safety profile, aluminum adjuvants are often considered as the "gold standard" against which newly developed adjuvants should be compared (HogenEsch et al, 2018). Studies have shown that there are various mechanisms by which ABAs contribute to immunogenicity of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the manufacturer, the type and aluminum content of vaccines licensed for use in the United States, varies. For instance, the Dtap vaccine manufactured by GSK (tradename Kinrix) contains ≤0.6 mg of aluminum present as aluminum hydroxide while Dtap vaccine manufactured by Sanofi-Pasteur (tradename Daptacel) contains 0.33 J o u r n a l P r e -p r o o f mg of aluminum present as aluminum phosphate (HogenEsch et al, 2018). It is thought that the amount of aluminum found in these vaccines poses a low risk of harm compared to its benefits (Mitkus et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another very interesting field that these structures may have applications is vaccinology. For almost 70 years aluminum salts are the “gold standard” for immunoadjuvants and are found in commercial vaccines against human papilloma virus, human hepatitis B virus, Bacillus anthracis and others . However, there is always the need to develop “stronger immunoadjuvants”, namely compounds that will elicit stronger immune reaction and, in addition, there are health issues associated with the use of aluminum compounds.…”
Section: Figurementioning
confidence: 99%